Prognostic significance of the pattern visual evoked potential in ocular hypertension. Issue 2 (February 1991) - Bray, L C; Mitchell, K W; Howe, J W
Abstract : This paper reports a prospective study on 49 ocular hypertensive patients to evaluate the prognostic significance of transient abnormalities in the pattern visual evoked potential (VEP) in the development of glaucoma. Seven of 24 patients with VEP abnormalities at diagnosis of ocular hypertension developed glaucomatous field defects in the follow-up period as compared with none of 25 patients with normal VEPs at diagnosis. We conclude that appropriately designed pattern VEP testing is a valuable complement to careful (preferably computerised, static) perimetry. In addition, our findings support the contention that, in glaucomatous disease of the optic nerve, rudimentary pattern processing mechanisms–that is 'Y'-type units of the magnocellular pathways–may be affected earlier than luminance processing mechanisms.